2020
DOI: 10.3390/ani10081384
|View full text |Cite
|
Sign up to set email alerts
|

The Milk Thistle Seed Cakes and Hempseed Cakes are Potential Feed for Poultry

Abstract: The aims of this work were to summarize the nutritional value of the milk thistle seed cakes and hempseed cakes and describe the influence on selected performance parameters, metabolism and animal health from inclusion of these non-traditional feeds into diets. It seems more appropriate to apply the extract of the bioactive substances complex to the livestock diets than addition of expellers or other forms of plants processing. The seed expellers, etc. mostly worsened the chickens’ performance parameters with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 63 publications
(107 reference statements)
1
25
0
Order By: Relevance
“…Phytogenic additives can prevent the development of stress-related health disorders within a normal feed dose [ 1 ]. A promising direction is the use of alternative feeds containing bioactive compounds or mixtures of natural origins or the use of phytoadditives or plant extracts, probiotics, prebiotics, symbiotics, or oilseed by-products in animal nutrition [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytogenic additives can prevent the development of stress-related health disorders within a normal feed dose [ 1 ]. A promising direction is the use of alternative feeds containing bioactive compounds or mixtures of natural origins or the use of phytoadditives or plant extracts, probiotics, prebiotics, symbiotics, or oilseed by-products in animal nutrition [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MT can also be used as a part of functional food for farm animals ( Table 1 ). MT oilseed cake is enriched in crude proteins, dietary fiber, and fat ( Stastnik et al, 2020 ). The seed cake contains ∼4% of flavonolignans ( Stastnik et al, 2020 ).…”
Section: Milk Thistlementioning
confidence: 99%
“…MT oilseed cake is enriched in crude proteins, dietary fiber, and fat ( Stastnik et al, 2020 ). The seed cake contains ∼4% of flavonolignans ( Stastnik et al, 2020 ). It has been reported that the addition of MT oilseed cake in the diet of lactating dairy cows in the amount of 25% of the required digestible protein increased the protein and fat content in the milk, improved its amino acid composition, and augmented the average daily milk yield ( Chabaev et al, 2011 ).…”
Section: Milk Thistlementioning
confidence: 99%
“…Herbs and herbal preparations contain active biological ingredients, i.e.,: essential oils, tannins, glycosides, flavonoids, terpenes, mucilages, and organic acids [5,[8][9][10]. Biological active components of herbal preparations display multi-directional activity: anti-stress, antibacterial, anti-virus, and anti-fungicidal [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, milk thistle (Silybum marianum [L.] Gaertn) is increasingly popular in animal nutrition [9,[19][20][21]. Milk thistle seeds have a different content of protein (160-300 g/kg) containing a lot of exogenous amino acids, which is confirmed by EAAI-the essential amino acid index (60.32) [22][23][24].…”
Section: Introductionmentioning
confidence: 99%